The Influence of Product Innovation and Prices on The Purchase Intention of Vivo Handphone Products in Anita Posel Pancur Batu Store - Said Maulana Ishak Sirait; Amrin Mulia Nasution; Sugito Sugito (Universitas Medan Area, 2022)
This study aims to find out whether Product Innovation has a significant effect on the intention to buy vivo cellphone products at the Pancur Batu anita cellphone shop, and to find out whether the price has a significant effect on the purchase intention of vivo cellphone products at the Pancur Batu cellphone anita store. The population in this research is the consumer of anita handphone shop. The sample in this study was 71 respondents using multiple linear regression analysis. The results of this study can be seen that Product Innovation (X1) has a significant positive effect on the purchase intention of vivo cellphone products at the Pancur Batu anita cellphone shop, Price (X2) has a significant positive effect on the purchase intention of vivo cellphone products at the Pancur Batu cellphone anita store.